(untitled) (Journal of Partial Differential Equations, 2024)
This paper considers the Cauchy problem of pseudo-parabolic equation with inhomogeneous terms u_t = ∆u+k∆u_t+w(x)u^p (x,t). In [1], Li et al. gave the critical Fujita exponent, second critical exponent and the life span for blow-up solutions under w(x) = |x|^σ with σ >0. We further generalize the weight function w(x) ∼ |x|^σ for −2